Optimization and modeling of extraction of solid coconut waste oil - Sulaiman, Sarina; Abdul Raman, Abdul Aziz; Aroua, Mohamed Kheireddine (Elsevier, 2013)
Solid coconut waste was produced after coconut milk extraction process and may still contain up to 24 wt.% oil content. In this work, extraction of oil from coconut waste using batch and soxhlet extractor was studied. Effect of particle size diameter, type of solvent and solvent to solid ratio on the kinetic and thermodynamic parameters; entropy, enthalpy and free energy of extraction were investigated. The maximum oil yields for soxhlet and batch reactor were 23.6% at 80 C and 21.9% at 65 C, respectively for particle size diameter <0.5 mm when hexane was used as solvent. The kinetic of coconut waste oil extraction was found to be a first order mass transfer model. The DG, DS and DH values were 10.94–13.35 kJ/mol, 33.10–39.57 J/mol K and 0.12–1.25 kJ/mol, respectively shows that the extraction process was spontaneous, irreversible and endothermic based on thermodynamic parameters.